Influence of Learners’ L1 Arabic and L2 French on the Acquisition of L3 English - Najjar, Nicolas (Curtin University, 2022)
The thesis contributes to the understanding of an under investigated phenomenon, namely the relative effects of transfer from a first language (L1/Arabic) and a second language (L2/ French) into a third language (L3/English). The unique feature of the study lies in its investigation of lexical and grammatical transfer in their positive and negative forms in Lebanese university students’ use of English. Another distinguishing criterion is that the native language is distant to the acquired ones, both of which are typologically similar.